SEMIOTIKA IKLAN POLITIK INDONESIA PASCA REFORMASI (Studi Kasus Iklan PPRN, Partai Demokrat, Partai Golkar dan PDIP-Perjuangan) - Sari, Dewi Kartika (KOMUNITAS)
This research was conducted because of the many problems of political advertising in the form of billboards that use pictures legislator candidates supported by the visualization of images the artist as an endorser of political advertising. The phenomenon of the use of photographs and photo artists candidate in political ads we encounter in the aftermath of reform. Before thereform era, we see only the logo image and the image of political parties only in billboard advertisements of political parties. The study, observed four billboard ads that use prospective legislators as endorsernya artist. Roland Barthess semiotic theory is used to analyze political ads is to know the meaning of the sign is coded and not coded in the four studied political advertising. Meanwhile, the methodology used is descriptive qualitative research methodology. By using this methodology, expected to know the meaning of the sign system that works on four political ads. Keywords: Semiotics, Meaning, Signs, and Political advertising